U.S. government funding of cooperative research and development in North America - Wagner, Caroline S.; Berstein, Nurith, 1968-; Rand Corporation; Science and Technology Policy Institute (Rand Corporation) (Santa Monica, CA : RAND, 1999)
Since 1993, U.S. government agencies have spent, on average, more than $100 million a year on research and development projects involving the participation of researchers from Canada and/or Mexico. These activities have been focused primarily on environmental, agricultural, and earth sciences, as well as biomedical and genetic research. The U.S. government's R&D relationship with these two countries, while having common scientific interests, differs in character: The R&D relationship with Canada has the quality of a partnership between equals. In contrast, the relationship with Mexico, while sound and growing, is not an equal exchange, being more formal and having more one-way transfer of information and assistance. Moreover, while the U.S. has an active cooperative relationship with Canada in both defense and space R&D (the areas where the U.S. spends the majority of its research funds), there is little of this type of activity with Mexico. A three-way science and technology foundation or commission could provide support to enhanced cooperation.
"Science and Technology Policy Institute."
Includes bibliographical references (p. 49).
Also available on the internet via WWW in PDF format.
Keywords: Research -- United States -- Finance; Research -- United States -- International cooperation